The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1080/09638288.2020.1826585
|View full text |Cite
|
Sign up to set email alerts
|

Living with a long-term health condition and seeking paid work: qualitative systematic review and thematic synthesis

Abstract: Purpose: An interplay of complex issues influence opportunities to gain paid work for people living with long-term conditions, but there are patterns that traverse the various contexts. Synthesising findings across qualitative studies can inform vocational rehabilitation approaches. Methods: Public consultation and PRISMA guidelines were used to develop a protocol and comprehensive search strategy. Seven databases were searched and results screened against inclusion criteria. Included studies investigated eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…When Ben failed, the explanation was the co‐owned company in which financial exposure required the extraordinary labour (and joy) of its partners. This pattern aligns with previous studies highlighting the importance of workplace factors and the response of employers, supervisors and human resource staff for accommodating workers with health problems and impairments (Abma et al, 2013; Cancelliere et al, 2016; Donker‐Cools et al, 2018; Fadyl et al, 2020; Kenny, 1998; MacEachen et al, 2006). In seeing workplace factors (related to own impairments) as decisive, the injured individuals’ stories also demonstrate the belief that it is beyond the scope of the professionals’ work to intervene in workplace factors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…When Ben failed, the explanation was the co‐owned company in which financial exposure required the extraordinary labour (and joy) of its partners. This pattern aligns with previous studies highlighting the importance of workplace factors and the response of employers, supervisors and human resource staff for accommodating workers with health problems and impairments (Abma et al, 2013; Cancelliere et al, 2016; Donker‐Cools et al, 2018; Fadyl et al, 2020; Kenny, 1998; MacEachen et al, 2006). In seeing workplace factors (related to own impairments) as decisive, the injured individuals’ stories also demonstrate the belief that it is beyond the scope of the professionals’ work to intervene in workplace factors.…”
Section: Discussionsupporting
confidence: 90%
“…Many people at the margins of the labour market struggle with long‐term illness or impairment (OECD, 2010). Therefore, employment services must be provided to them in conjunction with health care, social services and rehabilitation (Fadyl et al, 2020; Heidenreich & Aurich‐Beerheide, 2014). Avoiding job loss, providing accommodations and support in the workplace, supporting a person’s active participation in their rehabilitation processes, organising flexible and coordinated services and operating across institutional and organisational boundaries are all essential to the return‐to‐work process (Andersen et al, 2012; Cancelliere et al, 2016; Liaset & Lorås, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to test this assumption, and to fill in some of these possible gaps in the evidence subsequent to this overview, we undertook three additional systematic reviews on vocational interventions for people living with: (1) mild to moderate mental health conditions, (2) amputation and (3) progressive neurological conditions, and a fourth systematic review on vocational intervention for Indigenous people with long-term conditions living in a postcolonial context. 53 However, this revealed no further evidence relevant to this overview, except in the case of research involving people with mild to moderate mental health conditions, where we found low-quality evidence supporting the use of modified IPS approaches to help people gain paid work (RR 1.70; 95% CI 1.23 to 2.34). 54 There is therefore urgent need for further well-conduct experimental trials of vocational interventions for people living with long-term health conditions or disability.…”
Section: Discussionmentioning
confidence: 68%
“…55 We also recommend that when undertaking systematic reviews and studies of vocational intervention that a clear distinction is made between studies involving people who are returning to prior employment and those involving people who are unemployed and seeking new employment, since these two situations comprise quite different needs and challenges. 56 Regarding the quality of this overview, we conducted systematic searches based on a comprehensive search strategy. We have a high degree of confidence that it is unlikely that we missed important systematic reviews that may have substantively changed the conclusions of this overview.…”
Section: Discussionmentioning
confidence: 99%